1993
DOI: 10.1007/bf00215090
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of selection based on the animal model BLUP in a finite population

Abstract: Monte Carlo simulation was used to assess the long-term effects of truncation selection within small populations using indices (I=ωf+m) combining mid-parent [f=(a i+a d)/2] and Mendelian-sampling (m=a-f) evaluations provided by an animal model BLUP (a=f+m). Phenotypic values of panmictic populations were generated for 30 discrete generations. Assuming a purely additive polygenic model, heritability (h 2) values were 0.10, 0.25 or 0.50. Two population sizes were considered: five males and 25 females selected ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
48
0
9

Year Published

1994
1994
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 25 publications
9
48
0
9
Order By: Relevance
“…They showed that, in this way, inbreeding rates can be reduced with only a small loss in response. This also agrees with the results obtained by Toro and Silio (1993 (Dempfle, 1975;Verrier et al, 1993 (Nicholas, 1989). Theoretical work is needed to compare objectively the different procedures suggested to control rates of inbreeding and to find optimum schemes setting the genetic gains from selection against the losses due to inbreeding.…”
Section: Selection Intensity In Femalessupporting
confidence: 93%
“…They showed that, in this way, inbreeding rates can be reduced with only a small loss in response. This also agrees with the results obtained by Toro and Silio (1993 (Dempfle, 1975;Verrier et al, 1993 (Nicholas, 1989). Theoretical work is needed to compare objectively the different procedures suggested to control rates of inbreeding and to find optimum schemes setting the genetic gains from selection against the losses due to inbreeding.…”
Section: Selection Intensity In Femalessupporting
confidence: 93%
“…Verrier et al (1993) utilizaram simulação para verificar os efeitos da seleção a longo prazo em pequenas populações submetidas à seleção pelos valores genéticos preditos pelo BLUP sob modelo animal e observaram que, nas populações de pequeno tamanho, o efeito da oscilação foi maior, enquanto a variância genética decresceu rapidamente. Em contraste, em populações de tamanho maior, o efeito da oscilação não foi tão grande e a variância genética se manteve.…”
Section: Figure 6 -Observed Phenotypic Values Using Blup With Exclusiunclassified
“…Valor fenotípico mais eficiente a escolha dos melhores indivíduos para a reprodução, visto que são utilizadas todas as informações disponíveis dos parentes de candidatos à seleção, de forma a otimizar a resposta genética em curto prazo (Verrier et al, 1993). Robinson et al (1989) compararam o progresso genético, durante 20 gerações, resultante da avaliação dos animais com utilização do BLUP e de um índice de seleção.…”
Section: Valor Fenotípico Valor Fenotípicounclassified
“…Verificaram que, em geral, o BLUP proporcionou maior resposta genética do que o índice de seleção proposto. Verrier et al (1993), ao verificarem os efeitos da seleção, em pequenas e grandes populações, usando um índice de seleção BLUP e seleção individual, concluí-ram que a seleção com o BLUP maximizava o ganho genético em grandes populações.…”
Section: Valor Fenotípico Valor Fenotípicounclassified